Pertanggungjawaban Notaris Dalam Mengungkapkan Pemilik Manfaat (Beneficial Owner) Pada Pendirian Perusahaan - Bimo Kusumo Putro Indarto; Suraji Suraji (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This article aims to examine the Role and Responsibility of Notary Related to Disclosing Beneficial Owner Information in Company Establishment. This research is a prescriptive normative legal research, using the statutory approach method and conceptual approach. The legal materials used consist of primary and secondary legal sources, which are analyzed through literature study of documents or library materials, and interpreted using deductive reasoning techniques and syllogism. The result to be achieved is that the notary is responsible for recording and identifying the beneficial owner. The notary is responsible in this capacity for ascertaining the identity of the beneficial owners and ensuring that all information related to them is correctly and accurately recorded in the company's official documents. In addition to ensuring recording accuracy, notaries are also responsible for reporting beneficial owner information to the Ministry of Law and Human Rights through online reporting systems such as AHU Online and the Administration System for Legal Entities (SABH).